Role of Leucine-Rich Repeat–Containing G-Protein-Coupled Receptors 4–6 (LGR4–6) in the Ovary and Other Female Reproductive Organs: A Literature Review - Yu-Hsun Chang; Kun-Chi Wu; Kai-Hung Wang; Dah-Ching Ding (Cell Transplantation)
Leucine-rich repeat–containing G-protein-coupled receptors regulate stem cell activity and tissue homeostasis within female reproductive organs, primarily through their interaction with the Wnt/β-catenin signaling pathway. LGR4–6 are increasingly recognized for their roles in organ development, regeneration, and cancer. This review aims to provide a comprehensive overview of the roles of LGR4–6 in female reproductive organs, highlighting their significance in normal physiology and disease states, specifically in the context of ovarian cancer. LGR4 is essential for the proper development of the female reproductive system; its deficiency leads to significant reproductive abnormalities, including delayed menarche and follicle development issues. LGR5 is a well-established marker of stem cells in the ovary and fallopian tubes. It has been implicated in the pathogenesis of high-grade serous ovarian cancer. LGR6, while less studied, shares functional similarities with LGR5 and can maintain stemness. It contributes to chemoresistance in ovarian cancer. LGR6 is a marker for fallopian tube stem cells and is involved in stem cell maintenance and differentiation. LGR4–6 regulate the pathophysiology of female reproductive tissues. LGR4–6 are promising therapeutic targets for treating reproductive cancers and other related disorders. Molecular mechanisms underlying the functions of LGR4–6 should be studied.